TEKNIK PEMBUATAN MODIFIKASI LONG SPAN ADAMS CLASP PADA GIGI INSISIF SENTRAL: LAPORAN KASUS - Muhammad Naufal Faiq; Sianiwati Goenharto; Winda kusumawardani; Anisa Nur Halimah; Narta Nikita Indiani (Dentin, 2026)
Background: Malocclusion can affect the aesthetics and function of the oral cavity, thus requiring orthodontic treatment. In removable orthodontic appliances, treatment success is greatly influenced by the retention components. The Adams clasp is one of the retention components commonly used because it has good retention and can be modified. In cases requiring additional retention in the anterior region, a modified long span Adams clasp with an interproximal arrowhead can be used on the incisors. Objective: To describe the fabrication procedure of a modified long span Adams clasp with an interproximal arrowhead on the central incisors. Case: The patient was in the mixed dentition phase with Angle Class I malocclusion, maxillary and mandibular anterior crowding, 4 mm overbite, 2 mm overjet, rotation of teeth 12 and 22, and linguoversion of tooth 42. Treatment was initiated in the maxillary arch with a treatment plan involving extraction of teeth 53 and 63, followed by derotation of teeth 12 and 22. To support appliance stability, a long span Adams clasp was fabricated on teeth 11 and 21. Conclusion: The fabrication of the long span Adams clasp was performed by bending 0.7 mm wire, forming interproximal arrowheads on teeth 11 and 21, creating the clasp bridge, arrowheads on the distolabial undercuts, clasp arms, and tags. The acrylic plate was fabricated using the sprinkle-on method, followed by finishing and polishing to produce a stable, smooth, and comfortable appliance.Keywords : Adams clasp, long span Adams clasp, removable orthodontic appliance, retention component